The Impact of Digital Transformation and Social Media Marketing on Consumer Loyalty in E-Commerce Startups in East Java - Rizky Andrianto Apriandana; Agus Wiastono (STIEKOP MALANG PRESS, 2026)
Purpose – This study examines the impact of digital transformation, comprising technological integration, data-driven decision-making, and operational agility, and social media marketing, including content marketing, influencer engagement, and community building, on consumer loyalty among e-commerce startups in East Java, Indonesia. Design/methodology/approach – This study employed a quantitative research design using a structured online questionnaire distributed to 350 consumers who had made repeat purchases from e-commerce startups based in East Java, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships between digital transformation, social media marketing, and consumer loyalty. Findings – The results indicate that both digital transformation and social media marketing have significant positive effects on consumer loyalty. Social media marketing demonstrates a stronger direct effect on consumer loyalty, while digital transformation also has a significant indirect effect by enhancing the effectiveness of social media marketing activities. These findings indicate that technological and data capabilities can strengthen the impact of digital marketing initiatives in fostering consumer loyalty. Research limitations/implications – This study is limited to consumers who have made repeat purchases from e-commerce startups in East Java, Indonesia, which may constrain the generalizability of the findings to other regions, industries, or types of digital businesses. Future research could expand the geographical scope and examine other types of digital businesses, as well as incorporate longitudinal designs or additional variables such as customer experience, trust, personalization, and perceived value. Originality/value – This study contributes to the literature by integrating digital transformation and social media marketing perspectives in explaining consumer loyalty within the context of e-commerce startups. Its originality lies in demonstrating that digital transformation not only directly contributes to consumer loyalty but also strengthens the effectiveness of social media marketing, providing empirical evidence from the rapidly growing Indonesian startup ecosystem, particularly East Java.